De la caresse d’un rêve aux tortures d’un cauchemar : la lecture du testament par Utterson dans The Strange Case of Dr Jekyll and Mr Hyde de Robert Louis Stevenson - Samia OUNOUGHI (E-REA, 2011)
Studies on The Stange Case of Dr Jekyll and Mr Hyde often focus on the duality between the “two eponymous characters.” This article aims at orientating the real reader’s eye towards the reader in the text, for Stevenson’s novella is first and foremost a collection of texts the reception of which much depends on the reading of Jekyll’s will by J.G. Utterson.